Facing COVID-19 Between Sensory and Psychoemotional Stress, and Instrumental Deprivation: A Qualitative Study of Unmanageable Critical Incidents With Doctors and Nurses in Two Hospitals in Northern Italy - Testoni, Ines; Franco, Chiara; Gallo Stampino, Enrica; Iacona, Erika; Crupi, Robert; Pagano, Claudio (Frontiers in Psychology, 2021)
Background: The COVID-19 pandemic severely strained the already unprepared Italian healthcare system. This had repercussions on healthcare workers, stemming, in particular, from a lack of clear guidelines, adequate protective equipment, and professional preparedness. Such conditions were especially prevalent in Northern Italy. Objectives: This study aimed to examine COVID-19-related professional and psychoemotional stress among nurses and doctors in two hospitals in Northern Italy, along with the worst critical incidents affecting healthcare personnel. A parallel objective was to elicit healthcare professionals' opinions about what changes are needed in the healthcare system's operations, as well as about the relational/emotional skills that are needed to better manage relationships with patients in emergency situations. Participants: Snowball sampling was used to recruit participants and yielded 17 hospital professionals: six nurses (five female and one male) and 11 doctors (seven male and four female). Three of these professionals worked in intensive care and the others in different wards. All had close contact with COVID-19 patients. Methods: The study employed a qualitative research design, using in-depth interviews of 60 min each that were conducted via Skype video calls. The interviews were recorded and transcribed, then analysed. The qualitative analysis employed mixed methods to identify the most relevant and recursive themes from the interviews. Results: Four fundamental themes emerged from our analysis of the interview texts: (1) disorganisation and psychoemotional stress; (2) urgency and critical incidents; (3) everything surreal; and (4) disruptions in empathetic relationships with patients. Conclusions: Through our analysis of the interview narratives, we found that systematic and in-depth psychological training is needed to prepare professionals for (1) altered relationships with patients in emergencies; (2) use of exceptional medical equipment; (3) elaboration of new bioethical models suitable for disasters and pandemics; and (4) engagement with the themes of death and dying.